Effect of TiO2 on microphase development during phase separation and crystallization in Na2O–B2O3–SiO2 glass system. Issue 5 (28th December 2021) - Kwinda, Tovhowani Innocent; Enke, Dirk; Koppka, Sharon
Abstract: This study examines the incorporation of TiO2 into sodium borosilicate glasses and its effect on the formation of glassy and crystalline microphases. Glasses in the composition range: 7Na2 O–23B2 O3 –(70 ‐  X )SiO2 – X TiO2 (where X  = 0–14.6 mol.% TiO2 ) which exhibit phase separation were investigated. Raman studies confirm the formation of two different TiO2 coordinations depending on the molar content of TiO2 . Thermal properties of glasses are unaffected by TiO2 addition. The domain size of microphase development in TiO2 ‐containing glass indicates competition between phase separation and crystallization. Enrichment of titanium on the interphase between glassy microphases reduces the mass transfer and consequently limits the growth rate of glassy phases. This competes with the formation of anatase for which a nucleation‐controlled mechanism is proposed.